Peningkatan Produktivitas Produksi Sandal Jepit UD. Darmaji Melalui Analisis Kebutuhan Pegawai - Wulan Ayu Permatasari; Mundari, Siti (Universitas Kadiri, 2024)
High demand for sandals at UD. Darmaji. However, production cycle time is still long. This study determines the number of employees needed to meet accurate production capacity demand. The study used a quantitative approach with a motion study approach. The study population was the entire activity at UD. Darmaji. The sample was 8 activities in the sandal production process. The research instruments were observation forms and stopwatches. Data were collected through observation and time measurement. The data were analyzed using the motion study method to calculate cycle time, allowance time, performance rating, standard time, employee prediction, and cost comparison. UD. Darmaji has enough production capacity to meet demand for the next 6 months. However, the production cycle time is still long, especially in the activity of attaching the strap. To meet demand for the next 1 month, UD. Darmaji can use alternative 2 with 14 regular time employees for 9 hours per day. This alternative is cheaper and can improve efficiency and production productivity